Postoperative chemotherapy had no prognostic effect on early‐staged young ovarian cancer with unilateral resection. (10th October 2018) - Zhang, Xiaofei; Wang, Shuoer; Zhao, SongJiao; Sun, Yidi; Yang, Gong
Abstract: Postoperative chemotherapy has been widely used in the treatment of early‐staged ovarian cancer patients underwent unilateral resection, but the clinical decision mainly depends on the doctor's experience without a well‐defined guideline. This study used propensity score matching to analyze the effect of postoperative chemotherapy for early‐staged ovarian cancer patients underwent unilateral resection on prognosis. Patients of age 50 or younger than 50 with early‐staged ovarian cancer were explored from the Surveillance, Epidemiology, and End Results program database during 2000‐2018. Propensity score matching was used to randomize the dataset and reduce the selection biases. Univariate and multivariate cox proportional hazards models were utilized to estimate the necessity of chemotherapy. In univariate analysis of matched population, both the overall survival and cancer‐specific survival analysis showed that chemotherapy had no effect on the prognosis of early‐staged young ovarian cancer patients (Overall survival, P =  0.477; Cancer‐specific survival, P  = 0.950). In propensity‐adjusted multivariate analysis, chemotherapy still had no effect on both the overall and cancer‐specific survival probability after excluding the effect of all the confounding factors (HR = 0.863, CI = 0.587‐1.269, P  = 0.455; HR = 1.009, CI = 0.633‐1.607, P  = 0.970). Our study suggested that postoperative chemotherapy is not necessary for early‐staged young ovarian cancer patients with unilateral resection, as indicated by both the overall survival and cancer‐specific survival. Abstract : Postoperative chemotherapy has been widely used in the treatment of early‐staged ovarian cancer patients undergoing unilateral resection, but the clinical decision mainly depends on the doctor's experience without a well‐defined guideline. Our study suggested that postoperative chemotherapy is not necessary for early‐staged young ovarian cancer patients with unilateral resection, as indicated by both the overall survival and cancer‐specific survival.